A vida adolescente levada a sério : identidade teen e cultura das séries - Coutinho, Lúcia Loner (2016)
This thesis theme is identity in USA teen television series, known as Teen Dramas, a narrative genre created in the 90's that follows and suits itself to the changes in the television market. From Kellner's (2001) perspective of media culture, contextualized through Marcel Silva’s (2013) series culture, this work approaches this narrative genre, through five selected series (Beverly Hills, 90210, Buffy, the vampire slayer, Dawson’s Creek, Glee e Pretty Little Liars) from the changes in the narrative practices, of circulation and converging consumption, that gave visibility and brought TV series, in their diverse genres, to a relevant space inside media culture. Its importance is also highlighted by Ortiz’s (2000) cultural globalization, bringing, from elements of cultural consumption, a space for symbolic identification that goes beyond borders. Viewing such productions together with Mitell's concept of narrative complexity (2012-2013), that tries to analyze how these techno-cultural elements articulate to form contemporary series, with its particular production processes. Focusing especially in the narratives, we analyze the series through an identity politics, that determines which are the teenage identities privileged in this television format. We also analyze some of the common spaces in which these identities are articulated inside the narrative: family, school and in the different forms of relating inside the group of youngsters (friendship, romance and sexuality). Through this analysis we identify a moderate approach of adolescence, between rebelliousness and submission to social cultural rules. In fact, it points to a teenager in a constant struggle between adequacy and inadequacy to society, a reflexive, sensitive, teen, open to diversity. And at the same time, reflects the changes in the social and family structures in the past decades. Our approach to convergence, establishes it from the adaptation of the media industries to practices made possible by new connection technologies, and how they have, in fact, served to the expansion and marketing of such texts, but still promoting new experiences of consumption and community.